2019
DOI: 10.1016/j.bpobgyn.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Operative vaginal delivery and post-partum infection

Abstract: Over the past decade, there has been an increase in awareness of infections associated with pregnancy and delivery. The most significant cause of postpartum infection is caesarean section, with 20-25% of operations followed by wound infections, endometritis or urinary tract infections. Around 13% of women in the UK undergo operative vaginal delivery (OVD) with forceps or vacuum, which is also associated with an increased risk of infection, estimated at 0.7% to 16% of these deliveries. Despite this, previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 62 publications
1
8
0
1
Order By: Relevance
“…Risk factors for maternal sepsis can be easily recognised, including caesarean section and operative vaginal birth (forceps or vacuum extraction) 4, 6. Without prophylaxis, an estimated 20–25% of women have an infection following caesarean birth, 7 and up to 16% have an infection following operative vaginal birth 8 . There is strong evidence from a systematic review 7 in women giving birth by caesarean section, that the use of prophylactic antibiotics reduces the incidence of wound infection, endometritis, and serious maternal infection by 60–70%.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for maternal sepsis can be easily recognised, including caesarean section and operative vaginal birth (forceps or vacuum extraction) 4, 6. Without prophylaxis, an estimated 20–25% of women have an infection following caesarean birth, 7 and up to 16% have an infection following operative vaginal birth 8 . There is strong evidence from a systematic review 7 in women giving birth by caesarean section, that the use of prophylactic antibiotics reduces the incidence of wound infection, endometritis, and serious maternal infection by 60–70%.…”
Section: Introductionmentioning
confidence: 99%
“…Such interconnectedness of interventions and associated traumatic complication was probably the main reason for wrongly attributing postpartum infection to OVD. A literature review by Kamel and Khaled overemphasized the association of postpartum infection with OVD without giving emphasis to the commonly associated episiotomy and perineal tear [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than the infection rate reported in most other studies of complications following instrumental vaginal birth. 29 As noted previously, very few of these observational studies followed women beyond discharge, yet post-partum wound infections and endometritis have been reported to occur at a peak of 7 days post discharge in large data-linkage studies. 43 The ANODE trial shows very clearly a significant burden of confirmed or suspected infection and, most notably, both superficial and deep perineal wound infection after initial hospital discharge.…”
Section: Comparison With Existing Literaturementioning
confidence: 97%
“…28 There is, therefore, considerable scope for direct patient benefit from an effective preventative strategy. Other non-randomised studies suggest higher infection rates of up to 16%, 29 which would correspondingly lead to an even greater potential benefit from a preventative therapy.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation